BREAKING BLOCK AND PRODUCT CIPHERS - Carlson, Albert H.; Hiromoto, Robert E.; Wells, Richard B. (International Journal of Computing, 2014)
The security of block and product ciphers is considered using a set theoretic estimation (STE) approach to decryption. Known-ciphertext attacks are studied using permutation (P) and substitution (S) keys. The blocks are formed from two (2) alphabetic characters (meta-characters) where the applications of P and S upon the ASCII byte representation of each of the two characters are allowed to cross byte boundaries. The application of STE forgoes the need to employ chosen-plaintext or known-plaintext attacks.